PENGEMBANGAN PENDIDIKAN AGAMA ISLAM BAGI REMAJA MESJID DALAM ORGANISASI IKATAN REMAJA MESJID DI KECAMATAN PALU BARAT KOTA PALU - Muhammad Alim Ihsan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2015)
This research aim to know picture education of religion Islam to is adolescent mosque and development education of religion Islam through mosque youth's activity.This research represent research of survey. Population in this research counted 890 and people of sampel taken 50% that is 445 people. Data gathered by using kuesioner, and analysed by using percentage analysis.Result of analysis indicate that: (1) Education of religion of Islam to adolescent in Adolescent Tying organization Mosque in District of Town west Palu of Palu reside in category. This matter can be seen from adolescent attendance mosque follow activity, and adolescent situation mosque at the of following lesson, and (2) Development of education of religion of Islam through mosque youth's activity in District of West Town Palu of Palu reside in category. This matter can be seen from overtaking of official member, mosque youth's activity program, adolescent participation mosque, and role of local government